PENGARUH PENGALAMAN AUDITOR, TIME BUDGET PRESSURE, AKUNTABILITAS DAN KOMPLEKSITAS TERHADAP KUALITAS AUDIT (Studi Empiris BPKP RI Perwakilan Provinsi Riau) - Rizka Rakhmawati; Rita Anugrah; Supriono Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aimed to determine the influence of Auditor Experience, Time budget pressure, Accountability And Complexity Towards, Audit Quality at Audit Board Of the Republic Of Indonesia/ BPKP-RI Riau Province. The Population used was auditors who worked at the development and audit agency of the Republic Of Indonesia/ BPKP-RI in Pekanbaru totaling 36 auditors, with samples obtained many as 30 auditors, using sampling census sampling technique. The tool used statistical test is Statistical Product and Service Solution (SPSS) ver. 21. Windows and Microsoft Excel 2010. Result of research showed that: 1) auditor experience has significant effect on audit quality, 2) time budget pressure has significant effect on the audit quality, 3) accountability has significant effect on the audit quality, and 4) complexity has influence significant to audit quality.Keywords : Audit Quality, Auditor Experience, Time Budget Pressure, Accountability, Complexity.